Joint Simon effect in rats: Validation across two strains and exploratory analysis of the influence of familiarity - Noriko Katsu; Kazuo Okanoya (PLoS ONE, 2025)
Examining the influence of others on joint actions could clarify the basal mechanisms underlying social coordination in non-human animals. The joint Simon task is used for this purpose, and some non-human animals have demonstrated the joint Simon effect. However, previous investigations have only demonstrated the effect among familiar dyads despite the potential importance of social relationships for task performance. In this study, we investigated joint Simon effects using two rat strains (Wistar and Long-Evans) that differ in appearance. We performed exploratory testing to examine whether familiarity between dyads affects the size of the joint Simon effect. We compared the joint Simon effects that emerged when subjects (N = 8) were paired with familiar cagemates to when they were paired with stranger non-cagemates. After discrimination training, the rats performed the joint Simon task with two auditory stimuli (2 and 4 kHz tones). Rats showed a significant joint Simon effect when paired with a cagemate partner, replicating earlier findings. Although rats showed a greater compatibility effect when paired with cagemates than with non-cagemates, the small sample size and repeated dyads warrant cautious interpretation. Our findings suggest that the attention of rats is drawn to adjacent partners during a joint task, even in the absence of explicit benefits. The exploratory results on familiarity suggest the possibility that perceived similarity between partners induces a larger joint Simon effect in rats.